Pengaruh Model Pembelajaran Charakter Project Citizen Berbasis Outdoor, Minat Belajar dan Berfikir Kritis Terhadap Prestasi Siswa - Linda Kristinawati (Jurnal Penelitian dan Pendidikan IPS, 2019)
The purpose of this research 1) To know the influence of the outdoor based character project citizen learning model toward the students achievement of partially fifth grade students at Mutiara Harapan Elementary School Lawang; 2) To know the influence of learning interest toward students learning achievement of partially fifth grade students at Mutiara Harapan Elementary School Lawang; 3) To know the influence of critical thinking toward students learning achievement of partially fifth grade students at Mutiara Harapan Elementary School Lawang 4) To know the influence of outdoor based character project citizen learning model, students interest, and critical thinking toward students learning achievement of simultaneously fifth grade students at Mutiara Harapan Elementary School Lawang.Based on research objectives which basically research that is used including applied research. Applied research is aimed at solving practical life problems. As the techniques used in collecting data in this research are documentation and questionnaires. The analysis on this research using multiple regression analysis with the SPSS program for Windows.The result of this research showed that 1) The first hypothtesis test results obtained no significant influence from outdoor based character project citizen models toward students learning achievement of partially fifth grade students at Mutiara Harapan Elementary School Lawang. Data analysis result with pearson test obtained the coefficient correlation of 0,121 with significancy of 0,343. Therefore it can be said that the effect of X1 on Y is not significant. Ho accepted and Hi rejected. 2) The second hypothesis test obtained any significant influence from outdoor based character project citizen models toward students learning achievement of partially fifth grade students at Mutiara Harapan Elementary School Lawang. Data analysis result with pearson test obtained the coefficient correlation of 0,411 with significancy of 0,001. Therefore it can be said that the influence of X2 on Y is significant. Ho rejected and Hi accepted. 3) The third hypothesis test results obtained any significant influence of critical thinking toward students learning achievement of partially fifth grade students at Mutiara Harapan Elementary School Lawang. Data analysis result with pearson test obtained the coefficient correlation of 0,472 with significancy of 0,000. Therefore it can be said that the influence of X3 on Y is significant. Ho rejected and Hi accepted. 4) The fourth hypothesis test result say there is influence of outdoor study based character project citizen models, learning interest and critical thinking toward students achievement of simultaneously fifth grade students at Mutiara Harapan Elementary School Lawang. The value of the determinant coefficient (R) of 0,652 which means that the independent variable is outdoor based character project citizen models (X1), learning interest (X2), and critical thinking (X3) able to explain the dependent variable students achievement (Y) of 65,2% while the rest is 34,8% explained by another variable outside the model. It shows that the dependent variable has a significance influence.